হাজার বছরের বাংলাদেশ : ইতিহাসের অ্যালবাম - হাননান, মোহাম্মদ.; Haka, Maphidula; Husena, Ākhatāra (ঢাকা : সাহিত্য প্রকাশ, 1995)
One thousand years of Bangladesh history in pictures.
Includes bibliographical references (p. [188]).
In Bengali.
Keywords: Bangladesh -- History; Bangladesh -- History -- Pictorial works; Bengal (India) -- History; Bengal (India) -- History -- Pictorial works